Etching Ceramic Samples with Fast Argon Atoms - Alexander S. Metel; Sergey N. Grigoriev; Marina A. Volosova; Yury A. Melnik; Enver S. Mustafaev (Surfaces)
A new approach to stripping surface layers from ceramics with fast atoms is proposed. The existing beam sources do not allow for a stripping rate of more than a few µm/h to be achieved. Usually, an increase in the etching rate is associated with growing flux density and energy of fast atoms, which can heat the parts of the beam source up to an inadmissible temperature. In the present work, the etching rate was significantly increased at permanent flux density and energy due to an increase in the angle of incidence of fast atoms on the product surface. An increase in the angle of incidence from zero to 80° resulted not only in an increase in the etching rate by several times but also in simultaneous polishing of the surface to a high finishing class.